The Muslim conquest of the Italian city of Bari and the establishment of an Islamic emirate there during the third century AH/ninth century AD (Journal of Human Sciences, 2026)
The study addresses a modelof the Muslim naval expeditions, whose details were neglected by the sources of that era, and did not garner the attention of historians to the extent that they were almost consigned to oblivion, as we hardly find any mention of them except for a scant few lines written by the hands of scribes. This scant material motivated an intellectual pursuit to recover a lost history. The undertaking proved arduous, akin to carving in agate, in an attempt to extract testimony from that past regarding the nature of the expedition directed towards the city of (Bari) in Italy, situated on the coast of theUpgrade for entire file translation at  in conquering Sicily and making it a base in the Mediterranean Sea, this research focuses on the factors contributing to the conquest of that city, then its establishment as an Islamic emirate, and traces the causes of its fall and eventual disappearance. The problem centeredfocusin an attemptto investigatethe motives behind that invasion between secession from the Aghlabid state and expansion into southern Italy. Through the analytical method, we sought to shed some light with the limited available fragments and scant references which guided us to conceptualize the events and deduce the conclusions we reached in addressing the research problem, thuswe concluded from this thatthe invasion of the city of Bariwas the result of the political and economic circumstanceswhich the region experienced, and despite the independence of that emirate fromthe Aghlabidsthere remained a nominal subordination.